Unusual, Radical Treatment of Type A Aortic Dissection: A Case Report - Benvenga, Rossella M.; Bellino, Michele; Mastrogiovanni, Generoso; Triggiani, Donato; Citro, Rodolfo; Masiello, Paolo; Galasso, Gennaro; Piscione, Federico; Iesu, Severino (AORTA, 2020)
Type A aortic dissection, according to Stanford classification, is a surgical emergency with high morbidity and carries 56% of in-hospital mortality when surgical intervention is not performed. The surgical mortality at 30 days is 10 to 20%. The therapeutic goals are to replace the diseased ascending aorta and to treat or to monitor the distal aortic patent false lumen. When the dissection involves the aortic root and the architecture of aortic valve is normal, the surgical techniques used could be multiple: reinforce the aortic root and spare the native aortic valve or replace the aortic valve and the aortic root. The Florida sleeve technique has been developed to treat the aortic aneurysm, sparing the aortic valve in patients with connective tissue disease. Some case reports have described the use of this technique to treat an acute aortic dissection. In the following case, we present a single stage repair of the ascending aorta, aortic arch, and proximal intrathoracic aorta in a patient with Type A aortic dissection through the contemporaneous use of two techniques: Florida sleeve and Vascutek “Thoraflex” hybrid prosthesis. The use of these two techniques allows the repair/replacement of the proximal intrathoracic aorta, the sparing of the native aortic valve, the employment of a hybrid prosthesis to replace the supraortic vessels, and the creation of a descending aortic landing zone for later, distal intervention.
Keywords: aneurysm; dissection; open surgical management; Florida sleeve; frozen elephant trunk